Modern sector development: The role of exports and institutions in developing countries - Thomas Gries; Rainer Grundmann (Review of Development Economics, 2020)
A prospering modern sector is crucial for the successful long-term development in developing countries as it provides income and job growth for large shares of society. While this idea is widely accepted, there is, perhaps surprisingly, far less analysis about the exact determinants of this economic modernization process. In this article we empirically investigate whether international trade and institutions, both much discussed in the debates on general growth and development, are particularly important for the diffusion of production in the modern sector within developing societies. In a large cross section time-series sample, we provide robust estimation results that point to an important role of institutions and to a nonlinear impact of manufacturing exports. Our results, which are derived using a range of estimators and are ultimately less susceptible to endogeneity concerns, also provide interesting insights into the role of natural resources and official development aid.
Keywords: 330; developing countries; institutions; international trade; manufacturing growth; panel analysis